2022
DOI: 10.1080/19420862.2022.2151075
|View full text |Cite
|
Sign up to set email alerts
|

Restoring the biological activity of crizanlizumab at physiological conditions through a pH-dependent aspartic acid isomerization reaction

Abstract: In this study, we report the isomerization of an aspartic acid residue in the complementarity-determining region (CDR) of crizanlizumab as a major degradation pathway. The succinimide intermediate and iso-aspartic acid degradation products were successfully isolated by ion exchange chromatography for characterization. The isomerization site was identified at a DG motif in the CDR by peptide mapping. The biological characterization of the isolated variants showed that the succinimide variant exhibited a loss in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Therefore, protein therapeutics are generally stored under mildly acidic pH (4–6) conditions which in turn favor isomerization . Studies aimed at deciphering the factors that modulate Asp/Asn isomerization have shown that peptides and proteins containing nonbulky amino acids, primarily Gly, at the carboxyl side of Asn/Asp are more susceptible to isomerization and deamidation reactions. , CDRs and other regions of mAbs that are particularly flexible and/or have higher solvent accessibilities are also more prone to deamidation and isomerization. , …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, protein therapeutics are generally stored under mildly acidic pH (4–6) conditions which in turn favor isomerization . Studies aimed at deciphering the factors that modulate Asp/Asn isomerization have shown that peptides and proteins containing nonbulky amino acids, primarily Gly, at the carboxyl side of Asn/Asp are more susceptible to isomerization and deamidation reactions. , CDRs and other regions of mAbs that are particularly flexible and/or have higher solvent accessibilities are also more prone to deamidation and isomerization. , …”
Section: Introductionmentioning
confidence: 99%
“…Considering the impact of Asn/Asp isomerization, identification of the resulting isomerized residues is vital for unraveling disease mechanisms and for the comprehensive characterization of biotherapeutics prior to an investigational new drug application filing at the Food and Drug Administration or other foreign regulatory agency. , While deamidation results in a mass shift of 0.984 Da and can be easily detected using mass spectrometry (MS), isomerization is difficult to detect because there is no mass change associated with it. Several tandem MS (MS/MS)-based methods have been developed to address the challenging differentiation of Asp/ iso Asp in proteins. , In one of the earlier reports, low-energy CID was used to identify iso Asp peptides based on the presence of diagnostic b ( N – 1) + H 2 O ( N is the position of iso Asp) and y ( L – N + 1) – 46 ions ( L is the length of the peptide), depending on the location of the basic residue .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations